2010
DOI: 10.1016/j.tourman.2009.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Inherent complexity: Disability, accessible tourism and accommodation information preferences

Abstract: a b s t r a c tStudies have identified constraints with the way that accessible accommodation information is documented and marketed. Yet, no research has investigated the criteria that people with disabilities determine as 'important' to selecting accommodation and their preference for presenting this information. This paper presents the results of a survey (n = 566) to determine the relative importance of room selection criteria through the development of a 55-item Hotel Accessibility Scale. Four information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
225
0
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 268 publications
(257 citation statements)
references
References 37 publications
15
225
0
17
Order By: Relevance
“…Disability studies have begun to examine the 'nature of being' in a rehabilitative context, where an individual who is disabled through traumatic injury undergoes a process of re-embodiment as they learn to interact with enabling environments in their homes and localities, their assistive technology, negotiate the interpersonal attitudes around them and establish their new embodiment to become en-wheeled (Papadimitriou, 2008). In a tourism context, there is a complex interplay of impairment, disability and environment (Darcy, 2010;Packer, McKercher, & Yau, 2007), where the characteristics of the individual must always be considered within the nature of customer-service relations. Using a systems approach to tourism (Leiper, 2003), one can imagine how this complex interplay needs to be negotiated when the individual travels from the tourist-generating region, where they interact with their day-to-day enabling environments, attitudes and assistive technologies, to the tourist-destination (Dis)embodied air travel experiences region, where any one or all of the may be absent or disrupted during the travel chain.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Disability studies have begun to examine the 'nature of being' in a rehabilitative context, where an individual who is disabled through traumatic injury undergoes a process of re-embodiment as they learn to interact with enabling environments in their homes and localities, their assistive technology, negotiate the interpersonal attitudes around them and establish their new embodiment to become en-wheeled (Papadimitriou, 2008). In a tourism context, there is a complex interplay of impairment, disability and environment (Darcy, 2010;Packer, McKercher, & Yau, 2007), where the characteristics of the individual must always be considered within the nature of customer-service relations. Using a systems approach to tourism (Leiper, 2003), one can imagine how this complex interplay needs to be negotiated when the individual travels from the tourist-generating region, where they interact with their day-to-day enabling environments, attitudes and assistive technologies, to the tourist-destination (Dis)embodied air travel experiences region, where any one or all of the may be absent or disrupted during the travel chain.…”
Section: Literaturementioning
confidence: 99%
“…The studies included data collected via open-ended survey responses (n = 2600) and in-depth interviews (n = 19) (Darcy, 2004(Darcy, , 2010, an updated dataset of complaints cases (n = 673) brought under the Australian Disability Discrimination Act of which 41 are air-travel-related (Darcy & Taylor, 2009) and relevant media accounts of air travel experiences of TwD. The detailed methodologies for each of these studies are not presented in this article but can be read in conjunction with those individual articles.…”
Section: Research Design and Analysismentioning
confidence: 99%
“…However, it is not surprising that they are included in the same factor here, as the communication stage naturally follows the information preparation stage. Moreover, communication and information constraints have been a prevalent area of study in tourism for some time (Williams et al, 2006;Darcy, 2010). Many barriers arise during the preplanning and information stages (Blichfeldt and Nicolaisen, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on constraints for tourists with disabilities normally focus on a specific tourism sector, such as transportation (Poria et al, 2009) or accommodation (Darcy, 2010;Poria et al, 2011). For example, Poria et al (2011) identified challenges that individuals with disabilities face in hotels and the effort they have to make to surmount them.…”
Section: Travel Constraints For Tourists With Disabilitiesmentioning
confidence: 99%
“…These have included sport and leisure participation (Aitchison, 2003;Bailey, 2005;Darcy & Dowse, 2013;DePauw & Gavron, 2005;Devas, 2003;Smith, 1985;Tregaskis, 2003;Veal, Darcy & Lynch, 2013); tourism (Buhalis & Darcy, 2011;Veitch & Shaw, 2011); facility access (Landy, 2007;Lyberger & Pastore, 1998;Petersen & Piletic, 2006); and accommodation preferences (Darcy, 2010;Kim, Stonesifer, & Han, 2012). Additionally, while typically people with disabilities may be perceived as recipients of volunteer services, more recently there has been discussion of the inclusion of people with disabilities as volunteers, thus as providers of services, rather than recipients of volunteer services (Balandin, Llewellyn, Dew, & Ballin, 2006;Mjelde-Mossey, 2006).…”
mentioning
confidence: 99%